Physiological characteristics of women's cold constitution and effects of exercise - Fumio Yamazaki (Japanese Society of Physical Fitness and Sports Medicine, 2024)
About half of young Japanese women have a cold constitution, which heightens susceptibility to cold syndrome. In recent years, new findings on the physiological features of a cold constitution have increased. A cold constitution lowers the quality of daily life, so coldness and the related complaints need to be alleviated. Single dynamic exercise transiently relieves coldness via the warm-up effect. Exercise training decreases sensitivity to cold under normal temperature conditions and enhances peripheral cutaneous vasodilatory responses in young women with a cold constitution. This review provides an overview of the physiological characteristics of women's cold constitution and the acute and chronic effects of physical exercise as a countermeasure.